Pilot Study on the Reliability of the Coach's Eye: Identifying Talent Throughout a 4-Day Cadet Judo Camp - Roberts, Alexandra H.; Greenwood, Daniel; Humberstone, Clare; Raynor, Annette J. (Frontiers in Sports and Active Living, 2020)
A typical assumption found in talent identification literature is that different coaches, given the same athletes and circumstances, will identify the same subset of athletes as ‘talented’. However, while coaches play a major role during talent identification in practical sport settings, there is limited empirical research exploring the processes which underpin this. The purpose of this study was to explore the reliability of ‘the coach’s eye’ during the assessment of talent in a group of athletes. Specifically, this project compared inter-coach agreement between nine judo coaches (ages 35.8+10.6 years) with varying levels of experience (12.9+8.9 years) in the evaluation of 24 talented cadet judo athletes (13-15 years) at seven timepoints throughout a four-day development training camp. Without discussion of their scores with other coaches, coaches provided a single score representing each athlete’s ‘potential for future performance’ on an 11-point Likert scale at each timepoint. Scores from each coach were converted into rankings from 1-24 to create a normalized scale to facilitate comparison of athletes. Based on their rankings at each timepoint, athletes were placed into one of three evenly distributed groups (high, medium and low rank). Inter-coach agreement at each timepoint was determined by the number of coaches who ranked each athlete in the same group, categorized at three levels: 50%, 75% or 100% agreement. Overall results showed that at completion of the camp, coaches reached 100% agreement on only two athletes, both of whom were in the high rank group. When inter-coach agreement was set at 50%, 15 athletes (62.5%) were placed into like groups. The first timepoint at which coaches were able to differentiate between the majority of athletes was Timepoint 3 (end of day 2). The findings suggest that, in isolation, coaches do not agree on the talent or potential of athletes. This indicates that the ‘coach’s eye’ is subjective and variable, and, given the same context, there is poor inter-coach agreement in the identification of talented athletes. In turn, these findings may have significant implications for both future talent identification research and athlete selection processes by sport organizations.